Precise mapping of one classic and three novel GluRIIA mutants in Drosophila melanogaster. - Mallik, B.; Brusich, D.J.; Heyrman, G.; Frank, C.A. (microPublication Biology, 2023)
Mutation of the Drosophila melanogaster GluRIIA gene or pharmacological agents targeting it are commonly used to assess homeostatic synaptic function at the larval neuromuscular junction (NMJ). The commonly used mutation, GluRIIA [SP16] , is a null allele created by a large and imprecise excision of a P-element which affects GluRIIA and multiple upstream genes. Here we mapped the exact bounds of the GluRIIA [SP16] allele, refined a multiplex PCR strategy for positive identification of GluRIIA [SP16] in homozygous or heterozygous backgrounds, and sequenced and characterized three new CRISPR-generated GluRIIA mutants. We found the three new GluRIIA alleles are apparent nulls that lack GluRIIA immunofluorescence signal at the 3 [rd] instar larval NMJ and are predicted to cause premature truncations at the genetic level. Further, these new mutants have similar electrophysiological outcomes as GluRIIA [SP16] , including reduced miniature excitatory postsynaptic potential (mEPSP) amplitude and frequency compared to controls, and they express robust homeostatic compensation as evidenced by normal excitatory postsynaptic potential (EPSP) amplitude and elevated quantal content. These findings and new tools extend the capacity of the D. melanogaster NMJ for assessment of synaptic function.